Skin Keratins - Wang, Fengrong (Methods Enzymol, 2015)
Keratins comprise the type I and type II intermediate filament-forming proteins and occur primarily in epithelial cells. They are encoded by 54 evolutionarily conserved genes (28 type I, 26 type II) and regulated in a pairwise and tissue type-, differentiation-, and context-dependent manner. Keratins serve multiple homeostatic and stress-enhanced mechanical and nonmechanical functions in epithelia, including the maintenance of cellular integrity, regulation of cell growth and migration, and protection from apoptosis. These functions are tightly regulated by posttranslational modifications as well as keratin-associated proteins. Genetically determined alterations in keratin-coding sequences underlie highly penetrant and rare disorders whose pathophysiology reflects cell fragility and/or altered tissue homeostasis. Moreover, keratin mutation or misregulation represents risk factors or genetic modifiers for several acute and chronic diseases. This chapter focuses on keratins that are expressed in skin epithelia, and details a number of basic protocols and assays that have proven useful for analyses being carried out in skin.